Some aspects of RF discharge in the "U-3M" torsatron - Berezhniy, V.L.; Ocheretenko, V.L.; Pavlichenko, O.S.; Pinos, I.B.; Prokopenko, A.V.; Tsybenko, S.A.; Lozin, A.V. (Вопросы атомной науки и техники, 2007)
Studies were made into the behavior of frequencies and harmonic power of the RF field used for plasma production and heating in the “U-3M” torsatron.